Diel vertical migration, size distribution and photoprotection in zooplankton as response to UV‐A radiation. (7th August 2015) - Ekvall, Mikael T.; Hylander, Samuel; Walles, Tim; Yang, Xi; Hansson, Lars‐Anders
Abstract: The transparency regulator hypothesis (TRH) proposes that ultraviolet radiation (UVR) is a main driving force behind diel vertical migration (DVM) of zooplankton in clearwater systems. While previous studies have mainly studied DVM in relation to the TRH on a spatial scale across systems we here focus on long‐term trends in a single system in order to assess if UVR explains observed patterns in DVM. We show that the strength of DVM in Daphnia is to a large extent explained by UVR and we demonstrate a tipping point at which the UVR intensity drastically affects the strength of DVM in Daphnia . In contrast, the strength of DVM could not be explained by the level of UVR among calanoid copepods. The amount of photoprotective compounds did not differ between zooplankton found at different depths indicating that zooplankton do not change their vertical position in relation to the amount of accumulated photoprotective compounds. In addition, we show that both Daphnia and calanoid copepods display patterns of size structured migration.